The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/meq-11-2019-0246
|View full text |Cite
|
Sign up to set email alerts
|

Managing operations by a logistics company for sustainable service quality: Indian perspective

Abstract: PurposeThe purpose of this paper is to understand how logistics service providers manage their operations for sustainable service quality and operational excellence. This study is also trying to propose a framework for measuring service quality index along with some research propositions for analyzing service quality and operational excellence.Design/methodology/approachThe detailed case analysis on sustainable practices of Indian logistics service providers (LSPs) has been done on the basis of case study appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 86 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…Many e-retail businesses have been trying to attract new customers rather than maintaining existing customers. However, unique laws of e-retail supply chain have maintaining relationship with customers in a more important position than ever (Gupta & Singh, 2020;Hsu, Angeloudis, & Aurisicchio, 2018;Kassim, Abdullah, & logistics, 2010;Shi & Liao, 2013;G. Wang, Gunasekaran, Ngai, & Papadopoulos, 2016).…”
Section: Literature Review Empirical Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many e-retail businesses have been trying to attract new customers rather than maintaining existing customers. However, unique laws of e-retail supply chain have maintaining relationship with customers in a more important position than ever (Gupta & Singh, 2020;Hsu, Angeloudis, & Aurisicchio, 2018;Kassim, Abdullah, & logistics, 2010;Shi & Liao, 2013;G. Wang, Gunasekaran, Ngai, & Papadopoulos, 2016).…”
Section: Literature Review Empirical Review and Hypotheses Developmentmentioning
confidence: 99%
“…In addition, it is important to establish relationship marketing strategies that delivers superior value through logistics management in order to secure competitive advantage (Gupta & Singh, 2020;Huma, Ahmed, Ikram, & Khawaja, 2019;Murfield et al, 2017). Nevertheless, most of the academic research on logistics has been conducted only from an operational perspective, such as route design, cost-cutting and dispute research.…”
Section: Literature Review Empirical Review and Hypotheses Developmentmentioning
confidence: 99%
“…It has been observed that adoption and implementation of sustainable practices by Indian LSPs are at the initial stage and need more attention for successful implementation at a broader level (Mangla et al, 2017;Singh et al, 2016b). It has been found that the reduction in carbon emissions by reducing the fuel consumption can be a sustainable initiative in the logistics sector (Gupta and Singh, 2020a). Natural and renewable resources can be utilized as sustainable alternatives to overcome shortage of resources (Dubey et al, 2017;Sureeyatanapas et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Benefits of being sustainable have been explored by various authors (Azevedo et al, 2017;Majumdar and Sinha, 2018;Gupta and Singh, 2020a). There is a need to create more awareness about sustainability benefits among LSPs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transportation, besides a growing population and industrialization, increased the pollution significantly (Nakamura, 2004). Therefore, transportation systems need to be environmentally sustainable (Gupta and Singh, 2020). Even manufacturing organizations are trying to use the concept of reverse logistics for ensuring a sustainable transportation system (Agrawal and Singh, 2019).…”
Section: Introductionmentioning
confidence: 99%